ANALISIS HUKUM DAN MORAL TENTANG ABORSI DI TENGAH KONTROVERSI - Pabubung, Michael Reskiantio (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2021)
Law and moral are two different field of studies. Sometimes, they appear as rival when solving a problem. As a case study for sample, the researcher took abortion. Abortion is a hot topic so far, debated on almost every day, and become one of the goverments’s concern to make a policy for the countries. No doubt, abortion is a difficult moral problem. But abortion also belongs to law since it is playing in the field of human rights to protect and defend. Long debate between moral and law is as if essential in abortion. By using qualitative research through literature analysis, this essay give a balance between law and moral analysis. It comes to a conclusion that even always competing each other almost in every case, they are two of complementing elements. Law and morality are like a pair of wings flapping together reaching the authentic truth.